Efficient deletion of microRNAs using CRISPR/Cas9 with dual guide RNAs - Ijee, Smitha; Chambayil, Karthik; Chaudhury, Anurag Dutta; Bagchi, Abhirup; Modak, Kirti; Das, Saswati; Benjamin, Esther Sathya Bama; Rani, Sonam; Paul, Daniel Zechariah; Nath, Aneesha; Roy, Debanjan; Palani, Dhavapriya; et al. (Frontiers in Molecular Biosciences, 2024)
MicroRNAs (miRNAs) are short non-coding RNAs that play crucial roles in gene regulation, exerting post-transcriptional silencing, thereby influencing cellular function, development, and disease. Traditional loss-of-function methods for studying miRNA functions, such as miRNA inhibitors and sponges, present limitations in terms of specificity, transient effects, and off-target effects. Similarly, CRISPR/Cas9-based editing of miRNAs using single guide RNAs (sgRNAs) also has limitations in terms of design space for generating effective gRNAs. In this study, we introduce a novel approach that utilizes CRISPR/Cas9 with dual guide RNAs (dgRNAs) for the rapid and efficient generation of short deletions within miRNA genomic regions. Through the expression of dgRNAs through single-copy lentiviral integration, this approach achieves over a 90% downregulation of targeted miRNAs within a week. We conducted a comprehensive analysis of various parameters influencing efficient deletion formation. In addition, we employed doxycycline (Dox)-inducible expression of Cas9 from the AAVS1 locus, enabling homogeneous, temporal, and stage-specific editing during cellular differentiation. Compared to miRNA inhibitory methods, the dgRNA-based approach offers higher specificity, allowing for the deletion of individual miRNAs with similar seed sequences, without affecting other miRNAs. Due to the increased design space, the dgRNA-based approach provides greater flexibility in gRNA design compared to the sgRNA-based approach. We successfully applied this approach in two human cell lines, demonstrating its applicability for studying the mechanisms of human erythropoiesis and pluripotent stem cell (iPSC) biology and differentiation. Efficient deletion of miR-451 and miR-144 resulted in blockage of erythroid differentiation, and the deletion of miR-23a and miR-27a significantly affected iPSC survival. We have validated the highly efficient deletion of genomic regions by editing protein-coding genes, resulting in a significant impact on protein expression. This protocol has the potential to be extended to delete multiple miRNAs within miRNA clusters, allowing for future investigations into the cooperative effects of the cluster members on cellular functions. The protocol utilizing dgRNAs for miRNA deletion can be employed to generate efficient pooled libraries for high-throughput comprehensive analysis of miRNAs involved in different biological processes.